Quiet Quitting: the main reasons - Lopes, Isabel Cristina (2024)
The concept of "quiet quitting" can be explained as the behavior that employees have in their organization where they only carry out the tasks for which they were hired, sticking to the essentials only, not creating an emotional relationship and commitment to the organization. This study analyses the Quiet Quitting phenomenon, as well as the possible reasons that promote this state. The study showed that most people in the sample (78%) are not in a quiet quitting situation. Age presented itself as an influencing factor, as older people feel more in a position of quiet quitting. The lack of career progression, as well as decommitment and burnout, were identified as the main reasons for this phenomenon. The main contributions of this work are to understand the phenomenon of quiet quitting and what are the main reasons that lead to it happening, contributing to a development of knowledge of Human Resources professionals.